Kompetensi Kepribadian Guru Berbasis Pendidikan Karakter Dalam Kitab Adab al-Dunya wa al-Din Karya Imam Al-Mawardi - Dwi Irawan , wahendra; Jasminto; Salim, M. Nur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract : The problem that will be discussed in this study is about how Teacher Personality Competence is Based on Character Education in the book of Adab Al-Dunya wa Al-Din. Based on these problems, this study aims to find out how Teacher Personality Competence is Based on Character Education in the Book of Adab Al-Dunya wa Al-Din. Based on its characteristics, the research is library research which is classified as a qualitative research method. The approach used in this study is a qualitative approach, namely by emphasizing its analysis on the process of concluding comparisons and on the analysis of the dynamics of the relationship of the phenomena observed using scientific logic. Almost all research figures agree that data collection in qualitative research is done by interviews, observation and documentation studies. In the context of library research, the interviews and observations were changed to text and discourse analysis. Based on the results of the study which consisted of three research focuses, namely: First, Teacher Personality in the Book of Adab al-Dunya wa al-Din which contains things that need to be studied or maybe emulated about having humble qualities and not being arrogant, teaching the knowledge they know , knowing one's own capacity, practicing their knowledge, not being stingy with their knowledge and recognizing the potential of their students. Second, Character Education in the Book of Adab al-Dunya wa al-Din which contains things that need to be studied or maybe emulated by teachers about being not boring, being obedient and contributing to leaders and being assertive, maintaining the sanctity of material that is doubtful, teaching because hoping for the pleasure of Allah SWT, advising, loving, providing convenience and helping students, not being rude, insulting and taking their students for granted, and not making their students despair. Third, about matters relating to teacher personality competencies based on character education in the book Adab al-Dunya wa al-Din.